2018
DOI: 10.1029/2017jd028250
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Amplitude Mountain Waves in the Mesosphere Accompanying Weak Cross‐Mountain Flow During DEEPWAVE Research Flight RF22

Abstract: Mountain wave (MW) propagation and dynamics extending into the upper mesosphere accompanying weak forcing are examined using in situ and remote‐sensing measurements aboard the National Science Foundation/National Center for Atmospheric Research Gulfstream V (GV) research aircraft and the German Aerospace Center Falcon. The measurements were obtained during Falcon flights FF9 and FF10 and GV Research Flight RF22 of the Deep Propagating Gravity Wave Experiment (DEEPWAVE) performed over Mount Cook, New Zealand, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 103 publications
(212 reference statements)
2
45
0
Order By: Relevance
“…The FFT for each pass reveals spectral power centered around λ H ~ 220, 120, and 80 km, with the spectral power being most significant on the first and second passes. The λ H are consistent with observations at the flight level of the GV, and stratospheric lidar observations of MWs (Fritts et al, ), suggesting that these observed wavelengths are likely associated with MWs. As expected for MWs, all amplitudes for the λ H ~ 220, 120, and 80 km decay upon approach to the MW critical level near 90 km.…”
Section: Temperature and Mf Measurements And Validationsupporting
confidence: 88%
See 1 more Smart Citation
“…The FFT for each pass reveals spectral power centered around λ H ~ 220, 120, and 80 km, with the spectral power being most significant on the first and second passes. The λ H are consistent with observations at the flight level of the GV, and stratospheric lidar observations of MWs (Fritts et al, ), suggesting that these observed wavelengths are likely associated with MWs. As expected for MWs, all amplitudes for the λ H ~ 220, 120, and 80 km decay upon approach to the MW critical level near 90 km.…”
Section: Temperature and Mf Measurements And Validationsupporting
confidence: 88%
“…Assuming hydrostatic motions, the MF per unit mass for a given GW can be calculated as (Bossert et al, ; Ern et al, ; Fritts et al, ), MF=<uHw>=<12TtrueT¯gN2()kHm> where u H ′ and w ′ are the horizontal and vertical wind perturbations of the GW, k H and m are the horizontal and vertical wavenumbers, and braces denote the mean over the observation segment. While k H can be obtained from the FFT and corresponding spectral temperature amplitude calculation, m must be calculated using the dispersion relation (Fritts & Alexander, ), m2=N2()cUH214H2kH2 where c is the Earth‐relative phase speed assumed to be ~0 m/s for the observed presumed MWs and U H is the background wind in the direction of the MW horizontal wavenumber vector.…”
Section: Temperature and Mf Measurements And Validationmentioning
confidence: 99%
“…PMC observations have the potential to contribute to such a climatology at a specific season and altitude, but airglow data will be needed to address their statistics at other seasons and lower latitudes. In contrast, satellite characterization of GW variances spans all latitudes and seasons and large altitude ranges but is largely insensitive to the smaller‐ λ h and larger‐ ω i GWs expected to contribute most to energy and momentum deposition at all altitudes (Fritts, Vosper, et al, ; Preusse et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The campaign revealed that mesospheric activity and wave breaking was present on days where surface wind forcing was small. If the surface wind forcing was too large, the mountain wave would break in the stratosphere, due to having a large amplitude, and would dissipate before reaching the mesosphere (Ehard et al, ; Fritts et al, ; Kaifler et al, ). Despite significant advancement, very little is still known about the spectra and importance of nonprimary waves in the upper atmosphere.…”
Section: Introductionmentioning
confidence: 99%